Leadership Role In Nurturing Talent At Scientific Institutions - Ms. Hema Harsha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Measure of an organization’s success is not just limited to its financial performance but is reflected by the intellectual capabilities it has. In the present world wherein war for talent is a norm, identifying the right talent and nurturing them defines the success stories of sustained organizations. Leaders at various levels play a very important role in this whole process of identifying high potential candidates, nurturing them and creating a robust talent pipeline for the future.Good organizational branding can be done through robust talent management practices, right performance outcomes and a strong talent culture. This has to be espoused by efficient leadership which leverages on the intellectual assets, by cultivating and harnessing the competencies required for a continuous growth. Leader, as a talent steward has to identify critical talent, nurture individuals with such talent and ensure sustenance of such talent for futuristic use. Scientific institutions are an embodiment of highly competitive talented scientists. Designing high impact talent management activities should be the initiatives of top leaders of such organization in order to build a strong intellectual bank. For this the role of a HR executive is functional in nature, but the involvement of leaders is imperative in ensuring that the talent management challenges are addressed. This ensures that the organization transcends benchmarks in managing talent by reflecting talent culture as the foundation to nurturing right talent. Role of a leader as a talent steward and the impact of leadership on building scientific talent pipeline is the core of this study. This study is done with specific reference to the scientists in research institutions in India. Scientific leadership and its influence on nurturing scientific talent has not been studied so far. This study being exploratory and descriptive in nature tries to identify those components of leadership influencing talent identification, development and nurturing. To identify the potentially correlated variables, data was subjected to Principal Component Analysis (PCA).Impact of Leadership identified as one of the component has nine variables which show significant influence on talent nurturing. It was found that scientific leaders have an expanded critical role to cultivate talent internally by assessing talent and capabilities and identify emerging leaders. The findings suggest that Leadership can effectively leverage and deploy the identified nine variables and ensure better talent nurturing.